POWER RELATION IN MANAGEMENT OF NUSA DUA TOURIST RESORT, BALI - Purnaya, I Gusti Ketut; Ardika, I Wayan Ardika; Mudana, I Gede Mudana (E-Journal of Cultural Studies; Vol 8 No 3 (2015): Volume 8, Number 3, August 2015, 2015)
Nusa Dua Tourist Resort has been an important part of the development and growth of tourism industry in Bali. Therefore, the presents study was intended to analyze and answer the following questions: (1) what was the form of the power relation among the three stakeholders such as the government, the investors, and the local people in the management of the Nusa Dua Tourist Resort like after reformation from 1998 to 2013? (2) What ideologies contributing to the power relation in the management of the resort? (3) What was the meaning of the power relation among the three stakeholders such as the government, the investors and the local people, in such a management? It was found that the power relation in the management of the Nusa Dua Tourist Resort was affected by the hegemonic power, the negotiation power, and the oppositional power. The ideologies which contributed to the power relation in the management of the resort included the ideology of global tourism, the ideology of green tourism in the management of the resort and the ideology of the Local Culture in Culture Tourism. The struggle for the meaning of the power relation in the management of the resort among the three pillars (the government/BTDC, the investors, and the local people) would take place continuously. The three pillars gave different meanings, depending on their respective positions and interests.
Keywords: Nusa Dua tourist resort, power relation, hegemony, negotiation, oppositional, and ideology of global tourism.